Delayed perihematomal hypoperfusion is associated with poor outcome in intracerebral haemorrhage. (31st October 2021) - Morotti, Andrea; Busto, Giorgio; Boulouis, Gregoire; Scola, Elisa; Bernardoni, Andrea; Fiorenza, Alessandro; Amadori, Tommaso; Carbone, Federico; Casetta, Ilaria; Montecucco, Fabrizio; Fainardi, Enrico
Abstract: Background: The aim of this study was to characterize the temporal evolution and prognostic significance of perihematomal perfusion in acute intracerebral haemorrhage (ICH). Methods: A single‐centre prospective cohort of patients with primary spontaneous ICH receives computed tomography perfusion (CTP) within 6 h from onset (T0) and at 7 days (T7). Cerebral blood flow (CBF), cerebral blood volume (CBV) and mean transit time (MTT) were measured in the manually outlined perihematomal low‐density area. Poor functional prognosis (modified Rankin Scale 3–6) at 90 days was the outcome of interest, and predictors were explored with multivariable logistic regression. Results: A total of 150 patients were studied, of whom 52 (34.7%) had a mRS 3–6 at 90 days. Perihematomal perfusion decreased from T0 to T7 in all patients, but the magnitude of CBF and CBV reduction was larger in patients with unfavourable outcome (median CBF change −7.8 vs. −6.0 ml/100 g/min, p < .001, and median CBV change −0.5 vs. −0.4 ml/100 g, p = .010, respectively). This finding remained significant after adjustment for confounders (odds ratio [OR] for 1 ml/100 g/min CBF reduction: 1.33, 95% confidence interval [CI] (1.15–1.55), p < .001; OR for 0.1 ml/100 g CBV reduction: 1.67, 95% CI 1.18–2.35, p = .004). The presence of CBF < 20 ml/100 g/min at T7 was then demonstrated as an independent predictor of poor functional outcome (adjusted OR: 2.45, 95% CI 1.08–5–54, p = .032). Conclusion: Perihaemorrhagic hypoperfusion becomes more severe in the days following acute ICH and is independently associated with poorer outcome. Understanding the underlying biological mechanisms responsible for delayed decrease in perihematomal perfusion is a necessary step towards outcome improvement in patients with ICH.